2019
DOI: 10.3892/or.2019.7449
|View full text |Cite
|
Sign up to set email alerts
|

Niclosamide inhibits the cell proliferation and enhances the responsiveness of esophageal cancer cells to chemotherapeutic agents

Abstract: Niclosamide is an FDA-approved anthelmintic drug, and may elicit antineoplastic effects through direct STAT3 inhibition, which has been revealed in numerous human cancer cells. Chemotherapy is the standard treatment for advanced esophageal cancers, but also causes severe systemic side effects. The present study represents the first study evaluating the anticancer efficacy of niclosamide in esophageal cancers. Through western blot assay, it was demonstrated that niclosamide suppressed the STAT3 signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In addition, suppressing the activation of STAT3 was demonstrated to enhance the sensitivity to cisplatin ( 88 ). For commonly used chemotherapeutic drugs such as 5-fluorouracil (5-FU), cisplatin, and paclitaxel, the IC 50 values in EC cells were reduced when these drugs were combined with STAT3 inhibitors such as niclosamide ( 89 ). In addition to resistance to chemotherapy, STAT3 is involved in radioresistance as well.…”
Section: Pathological Roles Of Stat3 In Ecmentioning
confidence: 99%
“…In addition, suppressing the activation of STAT3 was demonstrated to enhance the sensitivity to cisplatin ( 88 ). For commonly used chemotherapeutic drugs such as 5-fluorouracil (5-FU), cisplatin, and paclitaxel, the IC 50 values in EC cells were reduced when these drugs were combined with STAT3 inhibitors such as niclosamide ( 89 ). In addition to resistance to chemotherapy, STAT3 is involved in radioresistance as well.…”
Section: Pathological Roles Of Stat3 In Ecmentioning
confidence: 99%
“…222 Niclosamide is an antihelminthic drug that has also demonstrated anti-cancer effects on several types of human cancer cells. [223][224][225] It has been more extensively investigated in experimental and clinical studies for individuals suffering from prostate and colorectal cancer. 226,227 Apart from its anti-neoplastic effects, niclosamide also demonstrated to inhibit TMEM16A and other members of the TMEM16 family.…”
Section: Tmem16a Inhibitorsmentioning
confidence: 99%
“…This effect resulted in the arrest of cells in the G0/G1 phase and induction of cell apoptosis [39]. Moreover, niclosamide potentiated the cytotoxic effects of some chemotherapeutic drugs, such as 5-FU, cisplatin and paclitaxel, thereby shifting their IC50 to lower doses with the ultimate result of reducing potential side effects in treated patients [39].…”
Section: Niclosamidementioning
confidence: 99%
“…More recent studies showed a protective effect of niclosamide in esophageal cancer [ 39 ]. In particular, niclosamide (2.5–10 μM) suppressed the STAT3 signaling pathway in esophageal adenocarcinoma cells (BE3) and esophageal squamous cell carcinoma cells (CE48T and CE81T) by impairing both STAT3 phosphorylation on Y705 residue and STAT3 protein expression.…”
Section: Anti-cancer Effects Of Anthelmintic Drugs In Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation